Transactivation of the Epidermal Growth Factor Receptor by Heat Shock Protein 90 via Toll-like Receptor 4 Contributes to the Migration of Glioblastoma Cells - Thuringer, Dominique (American Society for Biochemistry and Molecular Biology, 2011)
Extracellular heat shock protein HSP90α was reported to participate in tumor cell growth, invasion, and metastasis formation through poorly understood signaling pathways. Herein, we show that extracellular HSP90α favors cell migration of glioblastoma U87 cells. More specifically, externally applied HSP90α rapidly induced endocytosis of EGFR. This response was accompanied by a transient increase in cytosolic Ca(2+) appearing after 1–3 min of treatment. In the presence of EGF, U87 cells showed HSP90α-induced Ca(2+) oscillations, which were reduced by the ATP/ADPase, apyrase, and inhibited by the purinergic P(2) inhibitor, suramin, suggesting that ATP release is requested. Disruption of lipid rafts with methyl β-cyclodextrin impaired the Ca(2+) rise induced by extracellular HSP90α combined with EGF. Specific inhibition of TLR4 expression by blocking antibodies suppressed extracellular HSP90α-induced Ca(2+) signaling and the associated cell migration. HSPs are known to bind lipopolysaccharides (LPSs). Preincubating cells with Polymyxin B, a potent LPS inhibitor, partially abrogated the effects of HSP90α without affecting Ca(2+) oscillations observed with EGF. Extracellular HSP90α induced EGFR phosphorylation at Tyr-1068, and this event was prevented by both the protein kinase Cδ inhibitor, rottlerin, and the c-Src inhibitor, PP2. Altogether, our results suggest that extracellular HSP90α transactivates EGFR/ErbB1 through TLR4 and a PKCδ/c-Src pathway, which induces ATP release and cytosolic Ca(2+) increase and finally favors cell migration. This mechanism could account for the deleterious effects of HSPs on high grade glioma when released into the tumor cell microenvironment.